PERBEDAAN KUALITAS HIDUP PENDERITA GAGAL JANTUNG KONGESTIF DENGAN KOMORBID DIABETES MELITUS DAN KOMORBID HIPERTENSI - Haryati Haryati; Rahmawati Rahmawati (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Heart failure is a health problem with high mortality and morbidity rates in both developed and developing countries including Indonesia. It is a chronic disease that impairs the quality of lifeof patients and is associated with characteristics of demography and comorbid diseases. The presence of comorbid diseases can also affect the treatment of heart failure and worsen the symptoms and condition of heart failure. The aimed of this study was to determine the quality of life differences between Hypertension and Diabetes mellitus comorbid of congestive heart failure. This study was a comparative analytical study of 88 heart failure patients who sought treatment at cardiac clinic at RSUD Kota Kendari. The sampling technique was using purposive sampling based on predetermined criteria. Quality of life was measured using the Minnesota Living with Heart Failure (MLHF) questionnaire. Data analysis was performed using Mann Whitney U Test. with a confidence interval 0f 95% (alpha = 0.05). The result analysis showed a p-value 0.497. Conclusion showed that there was no quality of life diference between hypertension and diabetes mellitus comorbid with congestive heart failure in cardiac clinic at RSUD Kota Kendari. Thus, comorbid disease are not a factor affecting quality of life.